2020
DOI: 10.3390/su12104136
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Benefits of and the Barriers to the Switch to a Plant-Based Diet

Abstract: In recent decades, the food industry has been faced with new challenges, and it has had to develop new types of diets and produce new types of foods that can slow down the spread of chronic diseases. The aim of our research was to identify the characteristics of plant-based nutrition, based on international and Hungarian literature. The comprehensive analysis was performed based on the theoretical model called Theory of Planned Behavior, in the course of which the perceived and objective benefits of and barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 77 publications
3
109
0
7
Order By: Relevance
“…While plant-based, e.g., vegetarian, dietary patterns are generally perceived positively because of their benefits on health (CVD prevention) and the environment, there are also several barriers that hinder the switch to, and maintenance of a plant-based diet. Common barriers include health concerns that a plant-based diet may lack specific nutrients, reluctance to change dietary behavior, and enjoyment of eating meat and animal-based foods [99,100].…”
Section: Discussionmentioning
confidence: 99%
“…While plant-based, e.g., vegetarian, dietary patterns are generally perceived positively because of their benefits on health (CVD prevention) and the environment, there are also several barriers that hinder the switch to, and maintenance of a plant-based diet. Common barriers include health concerns that a plant-based diet may lack specific nutrients, reluctance to change dietary behavior, and enjoyment of eating meat and animal-based foods [99,100].…”
Section: Discussionmentioning
confidence: 99%
“…In a review, Fresán and Sabaté (2019) stated that not only environmental benefit but also human health benefit could be achieved by changing the current dietary patterns to plant-based diets. Numerous studies have indicated the health benefits associated with the replacement of animal sources of protein with plant-based proteins, including reduced risks of type 2 diabetes, heart diseases, and strokes (Fehér, Gazdecki, Véha, Szakály, & Szakály, 2020;Godfray et al, 2018). A model study even estimated a 6% to 10% reduction of global mortality rate, associated with the transition from heavy meat to plant-based diets (Springmann, Godfray, Rayner, & Scarborough, 2016).…”
Section: The Health Concerns Of Traditional Meat Consumptionmentioning
confidence: 99%
“…This leads to immense environmental pressure, diminishing biodiversity and rising environmental pollution, global warming and related adverse consequences [ 1 , 2 , 3 ]. Second, unhealthy lifestyle, which involves unbalanced nutrition and insufficient physical activity, has led to an increase in chronic diseases, metabolic syndrome, obesity and cancer [ 1 , 4 , 5 ]. In particular, high consumption of red meat has raised great concerns, due to its correlation with elevated morbidity and mortality rates [ 6 ].…”
Section: Introductionmentioning
confidence: 99%